Kajian Price Earning Ratio (Per) Saham Perusahaan yang Listing di BEJ Priode 2005-2006 - Iban Sofyan (Jurnal Ilmiah ESAI, 2008)
The purpose of this research is to give comprehensive information for investors about the share performance that are listed in Jakarta Stock Exchange (BEJ) in 2005-2006. Besides, the main motivation for the researcher to do this research is that Indonesian economic condition which is still in the monetary crisis. So that the research problems here are :(1) Are the total asset, debt to equity ratio (DER), return on equity (ROE), sales rating, and the earning per share growth significantly influence the price earning ratio?; (2) How is the relationship between each variables  examined to the price earning ratio (PER) ?The approaches used to see the value of the share in the Jakarta Stock Exchange (BEJ) is price earning ratio (PER). It’s based on the price ratio per -share with the earning per share (EPS) with constant growth model as assumption. The companies in this research are limited by : (1) a company that has listed in the BEJ at last from 2005 and registered up to 2006; (2) The company did not do any activities which influence the amount and the price of the share such as right issue, bonus share, stock split, dividend sharing, new share emission, and other policies.The results of this research are : (1) Classical evolution showed that there is no correlation between independent variables, and it can be seen from the regression result where the correlation with independent variables has no value bigger than 0,8. It shown that there is no multicolinerity between the relation of independent and dependent variables and it’s strengthened by hetroskedasities and autocorrelations test. It can be concluded that the model is free from the two classical deviations; (2)  the measurement of determination coefficient that R2 = 0,776 or 77,6 %,  it means 76,6 % independent variables can explain the dependent variables i.e. : PER; (3) based on the   F  evaluation,  it can be said that all variables ( Total asset, DER, ROE, Sales Rating, and  The EPS growth) significantly influenced the PER; (4) Based on the  t  evaluation  or evaluation of each variables, the fact shown that total asset variables, DER, ROE, and the EPS Growth variables proved to have  significant influences towards the PER variables and relation way which match to the theory.Keyword:   Price Earning Ratio Analysis.